PERANAN AL-JAM`IYATUL WASHLIYAH DALAM PENDIDIKAN - M Rozali (STIT Al-Ittihadiyah Labuhanbatu Utara, 2018)
The purpose of this study is to identify the history of standing Jam'iyyatul Washliyyah al ulama-ulamanya, as well as its role in the world of education. An editorial is not a Government which was established to unite the Muslims who have been dipecahbelah by the Netherlands colonizers. This study uses methodologi study historical documents where information – information relating to the history of the al Washliyah collected and later analysis and made a conclusion. The interview is also used to get the current information-information that concerned about education that are in al Washliyah. This study found that al Washliyah a lot of plays to educate the community through vocabulary-madrasa or school that they founded schools ranging from low to medium-sized school. While the curriculum which applies is stacked to approach mastery books the turath Al-Shaafa'i bermazhab. Washliyah also has a lot of bearing the scholars that now is given a significant role for the the advancement of Muslims and the State, not only in the territory of Indonesia, but also the territory formerly called Archipelago.